Manajemen Risiko Sistem Informasi Akademik pada SMA Panca Setya Menggunakan Metoda Octave Allegro - Utin Kasma (STIKes Ibnu Sina Ajibarang, 2024)
The success of implementing information systems in a school environment is significantly influenced by effective risk management. This research aims to implement the OCTAVE Allegro method to identify, assess, and manage risks associated with the information system at Panca Setya High School. The OCTAVE Allegro method was chosen for its systematic and structured approach to information security risk management.This research adopts a qualitative approach using a case study method. Data were collected through in-depth interviews with school staff, direct observations, and document analysis. The findings revealed several key risks threatening the information system at Panca Setya High School, including threats to student data confidentiality, weaknesses in technological infrastructure, and a lack of security awareness among users. Through the implementation of the OCTAVE Allegro method, this research successfully identified effective mitigation strategies, such as enhancing information security training for staff, updating security policies and procedures, and strengthening data protection technologies. The conclusion of this research highlights that comprehensive and sustainable risk management is crucial for protecting the school's information assets and ensuring operational continuity.The recommendations from this study are intended to assist the management of Panca Setya High School in enhancing their information system risk management, thereby better supporting the achievement of educational objectives.